Up from sin : a portfolio approach to financial salvation - Dodd, Randall (UN New YorkUS, 2005)
Suggests ways of raising capital in international markets by forming diversified portfolios of emerging market local currency debt issued by sovereign governments. Analyzes the implications of deploying such a policy for attracting capital to developing countries, the impact on the stability of their financial systems and on their costs of borrowing, and the implications for future development of local capital markets.